Yield and development of tomato crop using different water managements and water quality - Silva Junior, Josué Ferreira; Da Silva, Alexsandro Oliveira; Klar, Antonio Evaldo [UNESP]; De Freitas e Silva, Ilca Puertas; Tanaka, Adriana Aki (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
Incorrect irrigation management is one of the main factors of degradation in soil and low yield of crop. The experiment aimed at investigating the interaction between water deficit and salt stress on tomato’s growth. The experiment was conducted in pot under protected environment, on a completely randomized design in a 3 x 3 factorial scheme with 12 repetitions, with three levels of electrical conductivity in irrigation water (0, 3 and 5 dS m -1 ) and three levels of soil water potential (-10,-30 and-60 kPa). The variables analyzed were as follows: plant height, stem diameter, fresh and dry matter of aerial part, leaf area index, relative water content, number of fruits, weight of fruit and percentage of fruits with blossom-end rot. Data collections were performed at 75, 90, 105 and 120 days after sowing (DAS), exception for relative water content that occurred in the three most recent events. Results showed that water deficit influenced negatively the following variables: plant height (reduction of 16% and 27%), number of fruits, relative content of water in the leaves and percentage of fruit with rotting apical and that salt stress reduced, in a more accentuated way, the variables green phytomass (reduction of 40%) and dry matter (reduction of 47%), stem diameter, leaf area index and weight of fruit (reduction of 33% and 44%).
Produção e desenvolvimento da cultura do tomate submetida a diferentes estratégias de irrigação e qualidade da água
Keywords: Electrical conductivity; Salinity; Water deficit